Russian Binary Meters. Part Two. Chapter 9 - Kiril Taranovsky; Walter N. Vickery; Lawrence E. Feinberg (Studia Metrica et Poetica)
Editor's Note. Part I of Russian Binary Meters, the English translation of Kiril Taranovsky’s classic study Ruski dvodelni ritmovi (Taranovsky 1953), appeared in volume 7.2 (2020) of Studia Metrica et Poetica. Part I bears the title “Theoretical Bases for the Study of Russian Binary Meters”, and consists of the first four of the book’s nineteen chapters. Part II of Russian Binary Meters is entitled “Historical Development of the Rhythmic Drive of Russian Binary Meters”. Its first four chapters (numbered 5 to 8), devoted to trochaic tetrameter (four-foot trochee) and iambic tetrameter, trimeter and hexameter (four-, three- and six-foot iamb), were published in volumes 8.2 (2021) and 10.1 (2023). The next series of chapters (9 to 13) focuses on various types of iambic pentameter (five-foot iamb). Here we publish the introductory chapter of this series. The reader should bear in mind that the numbering of sections and footnotes is continuous with the earlier installments, beginning here with Chapter 9 and footnote 175.